Enumeration of Novel Lake Superior Cluster I (LSI) as a friction of the total picocyanobacteria in the autotrophic picoplankton (APP) Using quantitative real-time PCR. (c2009) - Andari, Jihad (2009)
Includes bibliographical references (leaves 58-67).